Improving adhesion of copper/epoxy joints by pulsed laser ablation. (January 2016) - Hernandez, Edwin; Alfano, Marco; Lubineau, Gilles; Buttner, Ulrich
Abstract: The purpose of the present work is to analyze the effect of pulsed laser ablation on copper substrates (CuZn40) deployed for adhesive bonding. Surface pre-treatment was carried using an Yb-fiber laser beam. Treated surfaces were probed using Scanning Electron Microscopy (SEM) and X-Ray Photoelectron Spectroscopy (XPS). The mechanical performance of CuZn40/epoxy bonded joints was assessed using the T-peel test coupon. In order to resolve the mechanisms of failure and adhesive penetration within surface asperities induced by the laser treatment, fracture surfaces were surveyed using SEM. Finite element simulations, based on the use of the cohesive zone model of fracture, were carried out to evaluate the variation of bond toughness. Results indicated that the laser ablation process effectively modifies surface morphology and chemistry and enables enhanced mechanical interlocking and cohesive failure within the adhesive layer. Remarkable improvements of apparent peel energy and bond toughness were observed with respect to control samples with sanded substrates.